PERLINDUNGAN HUKUM PEREMPUAN DI BIDANG POLITIK dalam Perjuangan Melawan Ketidakadilan Gender - Jati Nugroho (Muwazah, 2011)
The Constitution and the implementing regulations of the Constitution in the folosifis Indonesiai emphasis on equality and justice between men and women (equality and equity) through the development of the law with a cored Legal policy making and reform of the legal materials to suit your needs. But the normative contraction occurs when the Affirmative Policy in order to speed up justice and equality between men and women laiki has been canceled by the Constitutional Court’s decision to cancel the fifth paragraph of Article 205 of Law No.. 10 In 2008 the elected legislators decide the candidate by a majority vote. This clearly constitutes a waiver of gender inequality in the political sphere.